Efektivitas Metode Pembelajaran PAI Berbasis Digital Storytelling terhadap Penguatan Nilai Keislaman Siswa Generasi Z - Mubarak Marzuqi (Aafiyah: Jurnal Multidisiplin Ilmu, 2026)
The advancement of digital technology has significantly transformed educational paradigms, including Islamic Religious Education (IRE). Generation Z, as a digitally native cohort, requires learning approaches that align with their visual, interactive, and fast-paced information processing characteristics. This study aims to examine the effectiveness of the digital storytelling method in reinforcing Islamic values among Generation Z students. Utilizing a library research approach, this study analyzes educational theories, learner characteristics in the digital age, and prior research findings on the integration of digital media in religious education. The analysis reveals that digital storytelling is not only effective in enhancing students’ cognitive engagement but also addresses affective and spiritual dimensions. Beyond enriching the delivery of IRE content, this approach facilitates the internalization of Islamic values through meaningful and contextual narrative experiences. Therefore, digital storytelling holds potential as a strategic method in IRE that is responsive to the challenges of the digital era and the unique needs of Generation Z.